Ecological genetics of Italian peach‐potato aphid (Myzus persicae) populations in relation to geography, dispersal and insecticide resistance as studied using microsatellite and resistance markers. (12th July 2016) - Monti, Valentina; Loxdale, Hugh D.; Cesari, Michele; Frattini, Milo; Panini, Michela; Mazzoni, Emanuele; Manicardi, Gian Carlo
Abstract: Eight polymorphic microsatellites and two insecticide resistance markers ( kdr and R81T) were used to investigate the population genetics and demography of resistance mechanisms in field populations of the peach‐potato aphid, Myzus persicae (Sulzer), a global crop pest, in several areas of Italy, notably the north‐east, aiming to determine whether these parameters are linked to population structuring resulting from insecticide selective sweeps. Individuals collected directly from peach orchards (main primary host) in the spring, especially after control failure, revealed 90 microsatellite alleles, of which approximately one‐third were rare. Many populations deviated from Hardy–Weinberg expectations, in a few instances as a result of null alleles. F IS values were on average negative (indicating heterozygote excess), whereas F ST values (mean = 0.137) reflected moderate interpopulation gene flow, with nonstructured populations having an estimated higher level than insecticide‐treated ones. Population assignment and Mantel testing showed a non‐homogenous pattern, with some populations isolated genetically. Linkage disequilibrium was detected in four of the microsatellites and both resistance markers. Contrasting F ST patterns with resistance status supported the view that some populations were indeed structured. Neighbour‐joining trees revealed some populations to have similar insecticide resistance profiles, independent of geographical origin. Overall, the findings reveal that the natural M. persicae populations investigated in the present study, living within an intensively cultivated agro‐ecosystem, bear the signature of such management in terms of population structuring, as well as possibly also dynamics.